Surfactant science and technology - Myers, Drew, 1946- (John Wiley & Sons, Inc., 2020)
"This book provides a solid introduction to the study and use of surfactants, the molecular nature of the interactions of surface active materials, and the consequences their presence can have on system characteristics and performance. The book assumes no prior knowledge of the topic, and is aimed at students and professionals who need a basic understanding of the topic and its potential applications"- Resumé vydavatel
Keywords: chemie povrchových jevů; povrchově aktivní látky; surfactants; surface chemistry; elektronické knihy; monografie; electronic books; monographs